Digestive Oncology in the COVID-19 Pandemic Era - Brito,Mariana (2021)
Abstract: Introduction: Since the rise of the COVID-19 pandemic there has been widespread concern regarding the possible delay in the diagnosis/treatment of cancer patients. We aimed to assess the impact of the COVID-19 pandemic on the diagnosis, treatment, and outcome of patients with digestive cancer. Methods: This was a retrospective study including patients with an inaugural digestive cancer diagnosis discussed for the first time at our center during the weekly digestive oncology reunion (DOR) meeting. The study group was enlisted from March to August 2020, and a control group was sourced from the equivalent period of 2018. Patients with a previous digestive cancer diagnosis/discussion in the DOR were excluded. The following data were collected: demographics, referral origin, tumor staging, first DOR discussion timing, treatment, and outcome. Results: A total of 235 patients were included: 107 in the study group (65.4% male, mean age 71.59 years); 128 in the control group (54.7% male, mean age 68.16 years). The mean number of clinical discussions per week was higher in 2018 (13.65 vs. 10.67, p = 0.040), without a difference in the mean number of patients discussed for the first time (inaugural diagnosis) between groups (p = 0.670). In the 2020 study group, more patients were referred to DOR from the emergency room (ER), fewer from the outpatient clinic/hospital wards (p < 0.001), and more were referred after urgent surgery (p = 0.022). There was no difference in the mean waiting time from diagnosis to first DOR discussion (p = 0.087). Tumor staging in colorectal, gastric, and esophageal cancer was not significantly different between the groups (p = 0897, p = 0.168, and p = 0.717). More patients in the study group presented with stage IV pancreatic cancer (p = 0.043). There was no difference in the time span from DOR until the beginning of neoadjuvant chemotherapy (p = 0.680) or elective surgery (p = 0.198), or from surgery until adjuvant chemotherapy (p = 0.396). Also, there was no difference in 30-day mortality from the first DOR date between the groups (p = 0.742). Conclusion: During the COVID-19 era there was a reduced number of clinical discussions in the DOR, but the number of debated patients with an inaugural digestive cancer diagnosis was similar. In the study group more patients were referred to DOR from the ER, and were referred after urgent surgery, suggesting a delayed demand for clinical attention. Study group patients were not significantly affected by the pandemic regarding timely DOR discussion, beginning of treatment, or 30-day mortality, reflecting the maintenance of the quality of care for digestive cancer patients.